EPICARDIAL FAT MIMICKING PERICARDIAL TUMOURS: CASE SERIES AND REVIEW OF LITERATURE - Khan, Habib Rehman; Alatta, Ayman; Sosin, Michael (Journal of Ayub Medical College Abbottabad, 2019)
Advances in imaging modalities have improved diagnosis of diseases in patients allowing physicians to make earlier and accurate diagnosis with resultant improved overall outcome for patients. Sometimes, however this comes at a cost of over estimation of normal variants leading to further unnecessary investigations or in extreme cases interventions. In this article, we demonstrate three cases where epicardial fat is misdiagnosed as pericardial masses which is an example of misinterpretation of normal findings. Correct identification of pericardial fat on transthoracic echocardiograms is important in reducing misdiagnosis and also anxiety for both physicians and patients. knowledge about normal variants not only improve patients care but also reduce unnecessary investigations that are subsequently ordered for clarification. Keywords: epicardial fat; pericardial tumours; pericardial effusion; epicardial adipose tissue; EAT